(untitled) (CIPEEX, 2025)
The use of Artificial Intelligence (AI) in healthcare and medical education, from an academic and ethical perspective, has fostered changes in teaching and assessment practices. This article aims to report on the experience of the Family and Community Medicine module of the Medicine program at the Evangelical University of Goiás regarding the suitability of the reflective portfolio as a powerful element for provoking critical/reflective thinking and as an assessment tool. Given the challenges presented by the use of AI in the construction of pedagogical and assessment documents by medical students, we propose changing the format of the product, the frequency of delivery, and the assessment descriptors used. Artificial intelligence offers great advances in the medical field and in education and must be used responsibly and ethically. There is a need to rethink teaching practices so that active methodologies continue to stimulate the development of the skills necessary for medical training.